Photoredox Nucleophilic (Radio)fluorination of Alkoxyamines - Ortalli, S; Ford, J; Trabanco, AA; Tredwell, M; Gouverneur, V (American Chemical Society, 2024)
Herein, we report a photoredox nucleophilic (radio)fluorination using TEMPO-derived alkoxyamines, a class of substrates accessible in a single step from a diversity of readily available carboxylic acids, halides, alkenes, alcohols, aldehydes, boron reagents, and C–H bonds. This mild and versatile one-electron pathway affords radiolabeled aliphatic fluorides that are typically inaccessible applying conventional nucleophilic substitution technologies due to insufficient reactivity and competitive elimination. Automation of this photoredox process is also demonstrated with a user-friendly and commercially available photoredox flow reactor and radiosynthetic platform, therefore expediting access to labeled aliphatic fluorides in high molar activity (A m ) for (pre)clinical evaluation.